2020
DOI: 10.13057/biodiv/d210419
|View full text |Cite
|
Sign up to set email alerts
|

The alien freshwater fish of Mount Galunggung, West Java, Indonesia

Abstract: Abstract. Haryono, Wahyudewantoro G. 2020. The alien freshwater fish of Mount Galunggung, West Java, Indonesia. Biodiversitas 21: 1401-1408. Mt. Galunggung, located in West Java, Indonesia, is an active volcano renowned for its deadly eruption in 1982. This area has many waters bodies, but the fish communities have not been recorded, especially the alien or introduced fish species. Hence, the objective of the present study was to determine the alien fish diversity, abundance, local distribution and utilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Characterizations of meristic characteristics were done by counting eight items, followed by Hubbs and Lagler (1958) and Kottelat and Freyhof (2007) (Table 3). The results suggested that selected meristic characters are still within the range of previous studies (Haryono and Wahyudewantoro 2020;Azahar et al 2021). Intra-and inter-specific morphological variations can be highly affected by genetic and environmental factors and their interaction with them (Waiho et al 2021).…”
Section: Morphological Characteristicsmentioning
confidence: 51%
“…Characterizations of meristic characteristics were done by counting eight items, followed by Hubbs and Lagler (1958) and Kottelat and Freyhof (2007) (Table 3). The results suggested that selected meristic characters are still within the range of previous studies (Haryono and Wahyudewantoro 2020;Azahar et al 2021). Intra-and inter-specific morphological variations can be highly affected by genetic and environmental factors and their interaction with them (Waiho et al 2021).…”
Section: Morphological Characteristicsmentioning
confidence: 51%
“…Nam and Pham [218] also conducted mapping to determine the distribution of invasive yellow snail species and giant spiny catfish in Ca Mau province, Vietnam. The highly adaptive Cichlidae has become a dominant alien fish species and is abundant in the Mount Galunggung freshwater areas of Indonesia [219]. The Philippines has also encountered freshwater IAS fish species.…”
Section: Background On Invasive Alien Species Across Southeast Asiamentioning
confidence: 99%
“…Meanwhile, 19 introduced species are dominated by invasive species (Muchlisin, 2012). Haryono and Wahyudewantoro (2020) reported that 13 introduced species were in Galunggung areas.…”
Section: State Of Art Of Freshwater Fish Genetic Resourcesmentioning
confidence: 99%